OPTIMALISASI MODEL PENGELOLAAN BADAN USAHA MILIK DESA (BUMDes) SEBAGAI UPAYA DALAM MENINGKATKAN PENDAPATAN ASLI DESA - Komalasari, Intan; Sucihati, Roos Nana (Jurnal Ekonomi & Bisnis, 2024)
This study aims to analyze the Management of Village-Owned Enterprises (BUMDes) in Moyo Village, Moyo Hilir sub-District in order to increase the Village Own Source Revenue of Moyo Village, Moyo Hilir sub-District. The type of this study was qualitative study. The data used were primary and secondary data. The informants in this study were the Village Head, BUMDes Manager and the communities of Moyo Village. The method used to collect data were observation, interviews and documentation. The data analysis tool used was the theory of Miles and Huberman which consists of data collection, data reduction, data presentation and drawing conclusions. The results of study showed that the management had been done by Village-Owned Enterprises (BUMDes) in Moyo Village, Moyo Hilir sub-District was in accordance with the provisions set by the village government. In its implementation, the BUMDes in Moyo Village, had implemented management strategy aspects, such as planning, organizing, actuating and controlling. The management of BUMDes in Moyo Village, which is carried out by administrators by involving the government and village communities directly in every management activity, starting from planning, organizing, actuating and controlling, is expected to be able to encourage the community's economy so that can increase community income and contribute to increasing Village Own Source Revenue (PADes).